Meeting People Where They Are: Thriving Earth Exchange. Issue 5 (4th February 2014) - Galkiewicz, Julia; Pandya, Raj
<x xml:space="preserve">Abstract</x> As AGU develops the Thriving Earth Exchange, a new initiative to help scientists work with communities from all over the world to tackle local challenges, the main questions asked by AGU members and scientists are: How can I contribute to community‐inspired science when my research is about something totally unrelated? I know that my basic research will be important, but what if I want to make a difference right now?